Protic Stabilization Engenders High Energy Density and Long Cycle Life in Polyaniline–Zinc Supercapacitors - Shin, Chanho; Lee, Eun Hye; Eun, Hyeong Ju; Jung, Jinwook; Kim, Jong H.; Ng, Tse Nga (Small Science, 2024)
The redox activities of polyaniline (PANI) are hindered by the instability of pernigraniline salt (PS) state which degrades into oligo-aniline. In this work, the use of protic additives is examined to mitigate capacity fading and increase utilization of PANI in nonaqueous electrolytes. The protic additive propylene glycol, with its hydrogen-bonding capabilities, stabilizes the PS PANI and promotes reversible redox reactions, facilitating high capacity and an extended cycle lifetime for applications in metal ion supercapacitors. The use of this protic nonaqueous electrolyte in a PANI–zinc device results in an energy density of 255 Wh kg−1 at a power density of 1.8 kW kg−1 and a robust cycle lifetime of 3,850 charge/discharge cycles. The PANI at a high current density of 6.5 mA cm−2 reaches a capacity of 257 mAh g−1, equivalent to 87% of the its theoretical capacity, showcasing the effectiveness of the protic additive in improving both capacity and cycle life in electrochemical supercapacitors.
Keywords: polyaniline; supercapacitors; zinc ion capacitors